2021
DOI: 10.1186/s12879-021-06790-5
|View full text |Cite
|
Sign up to set email alerts
|

Application of mNGS to describe the clinical and microbial characteristics of severe burn a tanker explosion at a tertiary medical center: a retrospective study patients following

Abstract: Background Multiple organ dysfunction syndrome secondary to infection is the leading cause of death in burn patients. Bloodstream infection (BSI) and the prognosis of burn patients are negatively correlated. Metagenomic next-generation sequencing (mNGS) can detect many potential pathogens and may be more valuable for patients with severe burns. Methods We retrospectively explored the utility of mNGS in describing the clinical and microbial characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…In a prospective randomized controlled trial of 617 blood culture-positive patients, Banerjee et al [ 32 ] observed that multiplex PCR assay combined with the real-time antimicrobial stewardship could shorten the time from Gram staining to appropriate antimicrobial escalation or de-escalation. In 14 patients with severe burns, mNGS testing has also been shown to have potential value in the diagnosis of polymicrobial BSIs and can provide accurate guidance for antibiotic therapy [ 33 ]. In this study, we observed that the changes in pathogens load and number of species determined by ddPCR have potential value for guiding the use of antibiotics in critically ill patients with BSIs.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective randomized controlled trial of 617 blood culture-positive patients, Banerjee et al [ 32 ] observed that multiplex PCR assay combined with the real-time antimicrobial stewardship could shorten the time from Gram staining to appropriate antimicrobial escalation or de-escalation. In 14 patients with severe burns, mNGS testing has also been shown to have potential value in the diagnosis of polymicrobial BSIs and can provide accurate guidance for antibiotic therapy [ 33 ]. In this study, we observed that the changes in pathogens load and number of species determined by ddPCR have potential value for guiding the use of antibiotics in critically ill patients with BSIs.…”
Section: Discussionmentioning
confidence: 99%
“…Its performance for the detection of bloodstream infections is adequate, with one study reporting sensitivity and specificity of 87.1% and 80.2%, respectively [100]. It has also been shown to outperform blood culture for the detection of fungi and difficultto-culture bacteria, with Wu et al reporting an 87% pathogen detection rate compared to 59% for blood culture [101]. The usefulness of mNGS, particularly in detecting polymicrobial infections, has also been demonstrated in other related infectious diseases, such as pneumonia [102,103].…”
Section: Next-generation Sequencing (Ngs)mentioning
confidence: 99%